PENGEMBANGAN MODEL REHABILITASI BERBASIS MASYARAKAT (RBM) BAGI PENYANDANG CACAT KORBAN GEMPA BUMI TEKTONIK DI WILAYAH KABUPATEN BANTUL DAN SLEMAN - Purwandari Purwandari (Jurnal Penelitian Humaniora, 2009)
This Research has general purpose, which is to apply Community Based Rehabilitation for Disabled People of Tectonic Earthquake Victim for self-supporting life in rural. Specific purposes wishing to be achieved are (1) obtain rehabilitation model for disabled people, (2) form CBR team along with guidance package of CBR execution to empower the disabled people. The approach of research used Research and Development. First year, research is done for need assesment of disabled people and also survey of countryside potency for model test-drive. Second year draft of model development of guidance package of RBM program is compiled. Research Subject cover disabled people of earthquake victim residing in Countryside of Sendangtirto, Berbah, Sleman and Countryside of Srihardono, Pundong, Bantul. Research data collected through observation, interview, documentation, appraisal rural participatory. Data analysis is done by using technique of descriptive qualitative. Result of research show (1) Having been obtained countryside potency basic data in the region of research which is related to disabled people of earthquake victim, namely available covering of Human Resourches Development as CBR model developer, education service, health service, economic activities centre of citizen, home industry and company, (2) Having been obtained basic data of disabled people prevalensi number which need to get rehabilitation service, model test-drived countryside, namely 79 physical disabled people in countryside of Sendangtirto and 77 physical disabled people in countryside of Srihardono, (3) Having been formed team executor of CBR in countryside of Sendangtirto and Srihardono, each countryside is under the coordination of Kesra with 20 people of facilitators for each countryside, so that there are 40 people of facilitators which at the same time will become disabled people rehabilitation tutor, (4) Having been given training/tutorial about CBR to 40 people of facilitators at two countryside, (5) Having been earned to be blazed the way of fund income efforts to support program of RBM activity, that is fee managed by PKK, donator, and aid of NGO, (6) Occurrence of caring of the society to the importance of giving rehabilitation service for disabled people of earthquake victim after the clarification about program of CBR in the form of meeting and workshop.